2020
DOI: 10.1038/s42255-020-0209-6
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of NASH and hepatic fibrosis by the GLP-1R and GCGR dual-agonist cotadutide via modulating mitochondrial function and lipogenesis

Abstract: Non-alcoholic fatty liver disease and steatohepatitis are highly associated with obesity and type 2 diabetes mellitus. Cotadutide, a GLP-1R/GcgR agonist, was shown to reduce blood glycemia, body weight and hepatic steatosis in patients with T2DM. Here, we demonstrate that the effects of Cotadutide to reduce body weight, food intake and improve glucose control are predominantly mediated through the GLP-1 signaling, while, its action on the liver to reduce lipid content, drive glycogen flux and improve mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 61 publications
5
158
0
1
Order By: Relevance
“…Peptide therapy Synthetic OXM-104, cotadutide, and semaglutide (Synpeptide, Shanghai China) were dissolved in Phosphatebuffered Saline or 0.9 % NaCl for subcutaneous administration. The dose chosen for OXM-104 was based on in-house acute testing (Supplementary Figure S 2), while cotadutide and semaglutide doses were based on published studies 12,[18][19][20] . Aliquots were kept at -20 and thawed immediately before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide therapy Synthetic OXM-104, cotadutide, and semaglutide (Synpeptide, Shanghai China) were dissolved in Phosphatebuffered Saline or 0.9 % NaCl for subcutaneous administration. The dose chosen for OXM-104 was based on in-house acute testing (Supplementary Figure S 2), while cotadutide and semaglutide doses were based on published studies 12,[18][19][20] . Aliquots were kept at -20 and thawed immediately before use.…”
Section: Methodsmentioning
confidence: 99%
“…Dual GLP-1 and glucagon (GCG) receptor agonists are other types of candidates showing great potential as NASH treatment. Interestingly, a combination of these two peptide hormones not only reduces the hyperglycemic risk linked to GCG agonism but also provides promising hepatospecific effects 11,12 .…”
Section: Diomentioning
confidence: 99%
“…In rodent models, acute activation of GCGR improves whole-body glucose metabolism [105]. Additionally, hepatic GCGR stimulation also drives glycogen flux and improves mitochondrial turnover (Table 1) [106]. Thus, drugs that can enhance hepatic glucagon signaling may be potentially beneficial in treating NAFLD/NASH.…”
Section: Metabolic Functions Of Gpcrs In the Livermentioning
confidence: 99%
“…These data suggest that hepatic GCGR activation improves glucose tolerance by enhancing the action of insulin. It has also been reported that hepatic GCGR stimulation reduces lipid content, drives glycogen flux, and improves mitochondrial turnover and function [ 33 ]. This glucagon signaling pointing mechanism has high potential applications in new drugs for NAFLD/NASH.…”
Section: Role Of Gs-coupled Gpcrs In Liver Metabolismmentioning
confidence: 99%